2019
DOI: 10.1287/stsy.2018.0028
|View full text |Cite
|
Sign up to set email alerts
|

Uniformly Bounded Regret in the Multisecretary Problem

Abstract: In the secretary problem of Cayley (1875) and Moser (1956), n non-negative, independent, random variables with common distribution are sequentially presented to a decision maker who decides when to stop and collect the most recent realization. The goal is to maximize the expected value of the collected element.In the k-choice variant, the decision maker is allowed to make k ď n selections to maximize the expected total value of the selected elements. Assuming that the values are drawn from a known distribution… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
58
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 14 publications
6
58
0
1
Order By: Relevance
“…I show that this myopic regret is extremely easy to work with: it is simply a quadratic function of k when secretary valuations are uniformly distributed, and it is bounded by the probability of a binomial random variable being far out in its tail when secretary valuations have finite support. This latter fact yields a shorter and more direct proof of Arlotto and Gurvich's (2019) original result.…”
mentioning
confidence: 68%
See 4 more Smart Citations
“…I show that this myopic regret is extremely easy to work with: it is simply a quadratic function of k when secretary valuations are uniformly distributed, and it is bounded by the probability of a binomial random variable being far out in its tail when secretary valuations have finite support. This latter fact yields a shorter and more direct proof of Arlotto and Gurvich's (2019) original result.…”
mentioning
confidence: 68%
“…
Arlotto and Gurvich (2019) showed that regret in the multisecretary problem is bounded, both in the number of job openings, n, and the number of applicants, k, provided that the applicant valuations have finite support. I show that this result does not hold when applicant valuations are drawn from a standard uniform distribution.
…”
mentioning
confidence: 99%
See 3 more Smart Citations